2015
DOI: 10.1371/journal.ppat.1004896
|View full text |Cite
|
Sign up to set email alerts
|

The Myelin and Lymphocyte Protein MAL Is Required for Binding and Activity of Clostridium perfringens ε-Toxin

Abstract: Clostridium perfringens ε-toxin (ETX) is a potent pore-forming toxin responsible for a central nervous system (CNS) disease in ruminant animals with characteristics of blood-brain barrier (BBB) dysfunction and white matter injury. ETX has been proposed as a potential causative agent for Multiple Sclerosis (MS), a human disease that begins with BBB breakdown and injury to myelin forming cells of the CNS. The receptor for ETX is unknown. Here we show that both binding of ETX to mammalian cells and cytotoxicity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 98 publications
8
114
0
Order By: Relevance
“…Because MAL is required for ε-toxin binding to myelin in mice, we choose to evaluate the role of MAL in oligodendrocyte susceptibility to ε-toxin (37). MAL is a proteolipid expressed during late myelination in the CNS and plays a role in proper maintenance of CNS paranodes (38).…”
Section: Resultsmentioning
confidence: 99%
“…Because MAL is required for ε-toxin binding to myelin in mice, we choose to evaluate the role of MAL in oligodendrocyte susceptibility to ε-toxin (37). MAL is a proteolipid expressed during late myelination in the CNS and plays a role in proper maintenance of CNS paranodes (38).…”
Section: Resultsmentioning
confidence: 99%
“…Some proteins have been suggested as potential receptors for ETX such as hepatitis A virus receptor 1 (HAVCR1) 17 and the myelin and lymphocyte protein (MAL). 29 However, there is no sufficient evidence to confirm the identity of the receptor of ETX.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those of previous studies, which have shown that there is a putative protein receptor located at detergent resistant membrane (DRMs) in the apical cell membrane. 7,24,29,39 However, previous studies also showed that epsilon toxin was capable of forming channels in lipid bilayers without the need of a receptor, although with less efficiency. 21,25 We also found that rETX could occasionally form slight heptamer in PBS without cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rumah et al [84] showed binding of ETX to its target cells and its cytotoxic activity on mammalian cells are dependent on myelin and lymphocyte (MAL) protein. The pores formed by ETX include seven monomers of the toxin and some other proteins from the cell membrane, such as caveolin-1 and -2.…”
Section: Epsilon Toxin (Etx)mentioning
confidence: 99%